The Presence of a Play Space for Post Disaster Recovery - Sari, Novita; Kurniati, Euis; Evasufi Widi Fajari, Laksmi (Acta Pedagogia Asiana, 2023)
From the year 2000 to the year 2022, Indonesia has had a number of natural disasters that were big enough to be called "national disasters." After a natural disaster occurs, it has a significant physical and social impact. The Simple Multi Attribute Rating Technique (SMART) method is applied to determine the handling priority after a disaster due to the simple calculation process. The physical and psychological impacts caused by natural disasters in Indonesia are often ignored consciously. With the aim of normalization, it is necessary to repair and restore all aspects of public or community services as part of an effort to rehabilitate post-disaster areas. It is important to recognize the contribution to post-disaster reconstruction for victims who lost daily routine activities, emotional disturbance, family loss, and a sense of security. Trauma can be categorized as acute versus chronic and early versus late. The focus of this study was examining the presence of play spaces for post-disaster recovery. The hope is that this research aims to find out the extent of the presence of play spaces in providing services for post-disaster rehabilitation and reconstruction.